A Perceptual Approach to Cross-Cultural Counselling - Christensen, Carole Pigler (Canadian Journal of Counselling and Psychotherapy, 2011)
This paper presents a multi-dimensional model for cross-cultural counselling based on perceptual psychology concepts. The major premise is that the effectiveness of cross-cultural counselling is mutually dependent upon the counsellor's and the client's perceptions of each other, and of the counselling process itself. In addition to offering guidelines for counselling encounters, a number of propositions are outlined, which suggest directions for future research.